Transparent elastomeric nanocomposite blends
By using nanocomposite materials of surface-modified metal oxide nanoparticles and ethyl formate-based polymeric ester or copolyester, the problem of difficulty in finding a balance between mechanical properties and optical properties in the prior art is solved, and flexible display equipment materials with high transparency, low haze and high fold resistance are achieved.
Patent Information
- Application Number
- JP2024217137
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-07-30
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-10
AI Technical Summary
The prior art is difficult to provide the high mechanical properties and fold resistance required for flexible display devices while maintaining high visible light transmission and low haze.
A transparent nanocomposite material consisting of at least two ethyl formate polymeric or copolyester and surface modified metal oxide nanoparticles are used. These nanocomposites are surface modified to improve compatibility with polymer esters and enhance mechanical properties by the addition of nanoparticles.
A flexible display device material is achieved in high mechanical properties and fold resistance while maintaining high visible light transmission and low haze.
Smart Images

Figure 2025060675000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to transparent nanocomposites of polymer blends and surface-modified nanoparticles, and articles prepared with these transparent nanocomposite blends. [Background technology]
[0002] Displays and electronic devices are evolving to be curved, bent, or folded, providing new user experiences. These device architectures can include, for example, flexible organic light emitting diodes (OLEDs), plastic liquid crystal displays (LCDs), and the like.
[0003] To realize such flexible displays and to protect the display elements, flexible cover sheets or flexible window films replace traditional glass cover sheets. The flexible cover sheets have several design parameters, such as high visible light transmittance, low haze, and excellent scratch and puncture resistance to protect the elements contained in the display device. In some cases, the flexible cover sheets must be able to withstand thousands of folding operations with small bending radii (about 5 mm or less) without visible damage. In other cases, the flexible cover sheets must be able to unfold without leaving creases after being bent at high temperature and humidity. Summary of the Invention
[0004] The present disclosure relates to transparent nanocomposite blends of polymers and surface-modified nanoparticles, optical film articles, and optical articles prepared with these transparent nanocomposite blends, as well as methods of preparing the optical articles.
[0005] In some embodiments, the nanocomposite blend comprises at least two (meth)acrylic polymers or copolymers comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid, wherein the (meth)acrylic polymers or copolymers are miscible and at least partially neutralized, and a copolymer represented by Formula I. [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10 Alkyl groups and C1-C 10 A is selected from the group consisting of C1-C 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 and a surface-modified metal oxide nanoparticle that has been surface-modified with a surface modifier comprising a carboxylic acid silane, the linker group being selected from the group consisting of amide-containing groups.
[0006] Also disclosed is an optical film article. In some embodiments, the optical film article comprises at least one layer of a polymer nanocomposite blend, the polymer nanocomposite blend comprising at least two (meth)acrylic polymers or copolymers comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid, and surface-modified metal oxide nanoparticles, the (meth)acrylic polymers or copolymers being miscible and at least partially neutralized, and the surface-modified metal oxide nanoparticles being represented by the formula: [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10 Alkyl groups and C1-C 10 A is selected from the group consisting of C1-C 10Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 wherein the linker group is selected from the group consisting of amide-containing groups. In some embodiments, the optical film article is a multilayer article.
[0007] An optical article is also disclosed. In some embodiments, the optical article comprises a display device and an optical film article in contact with a surface of the display device. The optical film article comprises a flexible, bendable, rollable, foldable, or formable optical film. The optical film article is described above.
[0008] Also disclosed is a method of making an optical article, the method comprising preparing a nanocomposite blend, the nanocomposite blend comprising: (a) preparing an aqueous nano-dispersion of surface-modified metal oxide nanoparticles, the metal oxide nanoparticles being surface-modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of a first (meth)acrylic polymer or copolymer, the (meth)acrylic polymer or copolymer being at least partially neutralized; and (c) combining the dispersions of (a) and (b) to obtain a nanocomposite blend of the surface-modified metal oxide nanoparticles and the first (meth)acrylic polymer or copolymer. (d) forming an aqueous nano-dispersion of an acrylic polymer or copolymer; (d) drying and / or concentrating the nano-dispersion of (c); and (e) melt processing the dried and / or concentrated nano-dispersion (d) and a second (meth)acrylic polymer or copolymer to form a nanocomposite blend of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer, wherein the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer has been at least partially neutralized.
[0009] In some embodiments of making an optical article, the method includes preparing a nanocomposite blend, the nanocomposite blend comprising: (a) preparing an aqueous nanodispersion of surface-modified metal oxide nanoparticles, where the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of at least two (meth)acrylic polymers or copolymers, where the (meth)acrylic polymers or copolymers are at least partially neutralized; (c) combining the dispersions of (a) and (b) to form an aqueous nanodispersion of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer; (d) drying and / or concentrating the nanodispersion of (c); and (e) melt processing the dried and / or concentrated nanodispersion (d) to form a nanocomposite blend of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer, where the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer are at least partially neutralized.
[0010] In some embodiments, the nanocomposite blend is in the form of an optical film article as described above, which can be contacted with a surface of a display device to form an optical article as described above. [Brief description of the drawings]
[0011] The present application may be more fully understood from consideration of the following detailed description of various embodiments of the disclosure in conjunction with the accompanying drawings, in which: [Figure 1] 1 is a schematic side view of an exemplary flexible optical film of the present disclosure. [Diagram 2] 2 is a schematic side view of another exemplary flexible optical film of the present disclosure. [Diagram 3] 2 is a schematic side view of another exemplary flexible optical film of the present disclosure. [Figure 4]2 is a schematic side view of another exemplary flexible optical film of the present disclosure. [Diagram 5] 1 is a schematic side view of an exemplary flexible optical film on an optical display forming an article of the present disclosure. [Figure 6] FIG. 2 is a schematic side view of another exemplary optical film on an optical display forming an article of the present disclosure. [Figure 7] FIG. 1 is a schematic perspective view of an exemplary folded article including an exemplary flexible optical film of the present disclosure.
[0012] In the following description of the exemplary embodiments, reference is made to the accompanying drawings, which illustrate, by way of example, various embodiments in which the present disclosure may be practiced. It should be understood that the embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure. The drawings are not necessarily drawn to scale. Like numbers used in the drawings refer to like components. However, it should be understood that the use of a number to refer to a component in a particular drawing is not intended to limit the component in another drawing bearing the same number. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] A wide variety of substrates are used for optical articles that are relatively rigid. Among these substrates are materials such as glass plates, polymer plates such as polycarbonate and polymethylmethacrylate plates, etc. These rigid substrates are rigid and not flexible enough to be used in a wide range of new optical devices, so that they can have desirable optical transparency.
[0014] State-of-the-art display technology envisions flexible displays that are bendable, rollable, and even foldable, where the rigid glass solutions of current flat panel display electronics are not viable. Displays are also emerging in three-dimensional shapes that are amenable to molding. Plastics can be molded, but rigid glass cannot. To realize these advances in display technology, new display materials are needed.
[0015] New display materials must provide the historical benefits of glass, such as high visible light transmission and low haze, abrasion resistance, impact resistance, chemical resistance, and meet new demands for flexibility, such as folding around small bend radii, and the ability to withstand hundreds to thousands of folding movements without degrading properties. Ionic elastomers have some of the desired properties, such as high visible light transmission and low haze, chemical resistance, and flexibility. Being plastics, ionic elastomers also have the added advantage over glass of being moldable into three-dimensional shapes. However, these ionic elastomeric polymers lack the necessary mechanical characteristics or abrasion resistance, impact resistance, tensile modulus, etc.
[0016] Particulate fillers have been incorporated into polymers to improve their mechanical properties. However, most of the commercially available filled polymers are opaque and therefore unsuitable for use in optical articles. In addition, rigid particulate fillers can adversely affect the flexibility properties of the polymers with which they are combined.
[0017] One technique for providing modified properties is to blend polymeric materials. This approach can be problematic because preparation of a blend to improve one property, such as flexibility, can adversely affect other properties, such as optical properties. This is especially true for optical properties, since most polymer blends have at least some degree of immiscibility. Lack of miscibility can dramatically affect optical properties, such as visible light transmittance, haze, and transparency. Even polymers with the same or similar monomer composition can be immiscible, for example, if the polymers have different degrees of branching. Thus, modifying a polymer composition by blending it with another polymer, even if the polymers appear similar, is not straightforward, especially when the blended composition has the required optical properties.
[0018] The nanocomposite blends of the present disclosure achieve the competing goals of flexibility, optical transparency, and improved mechanical properties. The nanocomposite blends of the present disclosure, which may be referred to as "polymer nanocomposite blends," comprise a matrix that is a blend of at least two polymers and surface-modified nanoparticle fillers.
[0019] The nanocomposite blends of the present disclosure utilize metal oxide nanoparticles, which are particles having an average diameter in the nanometer range. These particles provide improved mechanical properties to the nanocomposite blends, and because of their small size, the nanoparticles do not scatter visible light. The nanoparticles can be surface modified to achieve compatibility with the polymer and avoid weak or strong agglomeration of the nanoparticles in the polymer nanocomposite blends, which leads to poor optical properties. The surface modifier is a carboxylic acid functional silane. Without wishing to be bound by theory, it is believed that the acid functionality on the surface modifier improves the compatibility of the particles with the acid functional (meth)acrylic polymer of the blend. A portion of the acid functionality on the surface modified nanoparticles may be neutralized, as may at least a portion of the acid functionality on the (meth)acrylic polymer.
[0020] Disclosed herein are nanocomposite blend compositions that are melt processable and optically transparent. These nanocomposite blend compositions can be used to form a wide variety of articles. The nanocomposite blend compositions include at least two different (meth)acrylic polymers or copolymers and surface-modified metal oxide nanoparticles, where the surface-modified metal oxide nanoparticles are surface-modified with a carboxylic acid functional silane surface modifier, and the (meth)acrylic polymers or copolymers are miscible and at least partially neutralized. Also disclosed herein are articles containing these nanocomposite blend compositions, as well as methods of preparing and using these nanocomposite blend compositions.
[0021] Unless otherwise indicated, all numbers expressing structural dimensions, quantities, and physical properties used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless specifically indicated to the contrary, the numerical parameters set forth in the above specification and appended claims are approximations that may vary depending upon the desired properties one of ordinary skill in the art would obtain utilizing the teachings disclosed herein. The recitation of numerical ranges by endpoints includes all numbers subsumed within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5) and any range within that range.
[0022] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include embodiments having plural referents unless the content clearly dictates otherwise. For example, reference to a "layer" includes embodiments having one or more layers. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the content clearly dictates otherwise.
[0023] As used herein, the term "adjacent" refers to two layers that are in close proximity to another layer. Adjacent layers may be in direct contact with each other or there may be an intervening layer. There is no empty space between adjacent layers.
[0024] As used herein, the terms "display film," "protective layer," "protective display film," "window film," "cover sheet," and "cover window film" are used interchangeably.
[0025] The terms "Tg" and "glass transition temperature" are used interchangeably, and the terms "Tm" and "melting temperature" are similarly used interchangeably. If measured, Tg or Tm values are measured by Differential Scanning Calorimetry (DSC) at a scan rate of 10°C / min unless otherwise indicated. Typically, Tg values of copolymers are not measured, but , as will be appreciated by those skilled in the art, are calculated using the well-known Fox equation using Tg values provided by monomer suppliers for homopolymers prepared from those monomers.
[0026] The terms "room temperature" and "ambient temperature" are used interchangeably and have their conventional meaning, i.e., a temperature between 20 and 25°C.
[0027] The terms "(meth)acrylic" and "(meth)acrylate" refer to polymers and monomers of acrylic or methacrylic acid, and alcohol esters of acrylic or methacrylic acid. Acrylate and methacrylate monomers and polymers are collectively referred to herein as "(meth)acrylate" or "(meth)acrylic". Polymers and copolymers described herein as (meth)acrylic or (meth)acrylate may contain additional ethylenically unsaturated monomers.
[0028] The terms "free radically polymerizable" and "ethylenically unsaturated" are used interchangeably and refer to a reactive group that contains a carbon-carbon double bond that can be polymerized via a free radical polymerization mechanism.
[0029] The term "polymer" is used herein consistent with common usage in chemistry. A polymer is a macromolecule composed of many repeating subunits. The term polymer includes homopolymers, i.e., polymers formed from one type of monomer, and copolymers, where the polymer is formed from two or more copolymerizable monomers.
[0030] The terms "miscible" or "miscibility" refer to at least two polymers that are compatible with each other such that a blend of the at least two polymers does not phase separate to form phase-separated microdomains large enough to produce significant scattering of visible light (wavelengths of about 400 to about 700 nm).
[0031] The terms "immiscible" or "immiscible" refer to at least two polymers that are incompatible with each other such that a blend of the at least two polymers phase separates to form phase-separated microdomains large enough to produce significant scattering of visible light (wavelengths of about 400 to about 700 nm), resulting in unacceptable haze.
[0032] The term "alkyl" refers to a monovalent group that is a radical of an alkane, which is a saturated hydrocarbon. An alkyl can be linear, branched, cyclic, or a combination thereof and typically has 1 to 20 carbon atoms. In some embodiments, an alkyl group contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, cyclohexyl, n-heptyl, n-octyl, and ethylhexyl.
[0033] The term "alkoxy" refers to a monovalent radical of the type --OR, where R is an alkyl group.
[0034] The term "aryl" refers to a monovalent group that is aromatic and carbocyclic. An aryl can have 1 to 5 rings that are connected or fused to the aromatic ring. Other ring structures may be aromatic, non-aromatic, or combinations thereof. Examples of aryl groups include, but are not limited to, phenyl, biphenyl, terphenyl, anthryl, naphthyl, acenaphthyl, anthraquinonyl, phenanthryl, anthracenyl, pyrenyl, perylenyl, and fluorenyl.
[0035] The term "alkylene" refers to a divalent group that is a radical of an alkane. Alkylene may be linear, branched, cyclic, or a combination thereof. Alkylene often has 1 to 20 carbon atoms. In some embodiments, alkylene contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. The radical centers of the alkylene can be on the same carbon atom (i.e., an alkylidene) or on different carbon atoms.
[0036] The term "heteroalkylene" refers to a divalent group that includes at least two alkylene groups connected by thio, oxy, or -NR-, where R is alkyl. The heteroalkylene may be linear, branched, cyclic, substituted with alkyl groups, or combinations thereof. Some heteroalkylenes are polyoxyalkylenes, where the heteroatom is oxygen, e.g., -CH2CH2(OCH2CH2) n OCH2CH2-, etc.
[0037] The term "arylene" refers to a divalent group that is carbocyclic and aromatic. The group has 1 to 5 rings that are connected, fused, or a combination thereof. The other rings may be aromatic, non-aromatic, or a combination thereof. In some embodiments, the arylene group has up to 5 rings, up to 4 rings, up to 3 rings, up to 2 rings, or one aromatic ring. For example, the arylene group may be phenylene.
[0038] The term "heteroarylene" refers to a divalent group that is carbocyclic, aromatic and contains a heteroatom such as sulfur, oxygen, nitrogen, or a halogen, such as fluorine, chlorine, bromine, or iodine.
[0039] The term "aralkylene" refers to a group of the formula: a -Ar a -[wherein, R a is alkylene, and Ar a refers to a divalent group in which the alkyl group is an arylene (i.e., an alkylene is bonded to an arylene).
[0040] The term "alkaryl" refers to a group of the formula: -R a -Ar a -[wherein, R a is alkylene, and Ar a is aryl (i.e., an alkylene is bonded to an aryl).
[0041] Unless otherwise indicated, "optically transparent" refers to a layer, film, or article that has high light transmission over at least a portion of the visible light spectrum (about 400 to about 700 nm). Typically, an optically transparent layer, film, or article has a luminous transmission of at least 80% and a haze value of 10% or less.
[0042] Unless otherwise indicated, "optically clear" refers to a layer, film, or article that has high light transmission across at least a portion of the visible light spectrum (about 400 to about 700 nm) and exhibits low haze. Typically, an optically clear layer, film, or article has a visible light transmission value of at least 80%, often at least 90%, and a haze value of 5% or less, 4% or less, and often 3% or less. Luminous transmission and haze can be measured using techniques described in the Examples section.
[0043] As used herein, the term "nominally colorless" means *This refers to a composition that is generally neutral on the yellow index, with a value of less than 5 or less than 3.
[0044] As used herein, "dispersion" refers to one or more (meth)acrylic polymers or copolymers dispersed in water, where the one or more (meth)acrylic polymers or copolymers are at least partially neutralized.
[0045] As used herein, "nanodispersion" refers to a liquid colloidal dispersion of metal oxide nanoparticles, where the liquid medium is water, an organic solvent, or a combination thereof, and where the nanodispersion may or may not include one or more (meth)acrylic acid polymers or copolymers.
[0046] As used herein, the terms "nanocomposite" and "polymer nanocomposite" are used interchangeably and refer to a composition comprising a polymer matrix having metal oxide nanoparticles dispersed therein.
[0047] As used herein, the terms "nanocomposite blend" and "polymer nanocomposite blend" are used interchangeably and refer to a composition comprising a polymer matrix of at least two polymers having metal oxide nanoparticles dispersed therein.
[0048] As used herein, "surface-modified nanoparticles" refers to metal oxide nanoparticles having a surface that is not chemically altered. In the case of colloidal silica, the unmodified nanoparticle surface is primarily silanol groups, Si-OH.
[0049] As used herein, "surface-modified nanoparticles" refers to metal oxide nanoparticles having a surface that has been chemically altered or surface modified.
[0050] As used herein, "silica" refers to amorphous silicon dioxide.
[0051] As used herein, "adhesive" refers to a polymeric composition that is useful for adhering two adherends together. Examples of adhesives are pressure sensitive adhesives and heat activated adhesives.
[0052] Pressure sensitive adhesive compositions are well known to those skilled in the art to possess properties including: (1) aggressive and persistent tack, (2) adhesion with no more than finger pressure, (3) sufficient ability to hold the adherend in place, and (4) sufficient cohesive strength to remove cleanly from the adherend. Materials that have been found to function well as pressure sensitive adhesives are polymers that are designed and formulated to exhibit the necessary viscoelastic properties to provide the desired balance of tack, peel adhesion, and shear retention. Obtaining the right balance of properties is not a simple process.
[0053] Heat-activated adhesives are non-tacky at room temperature, but become tacky at elevated temperatures, allowing them to bond to a substrate. These adhesives usually have a Tg or Tm that is higher than room temperature. When the temperature is raised above the Tg or Tm, the storage modulus usually decreases and the adhesive becomes tacky.
[0054] Disclosed herein is a nanocomposite blend composition comprising at least two different (meth)acrylic polymers or copolymers and surface-modified metal oxide nanoparticles, where the surface-modified metal oxide nanoparticles are surface-modified with an acid-functional silane surface modifier, and the (meth)acrylic polymers or copolymers are miscible and at least partially neutralized. Typically, the nanocomposite blend composition is melt-processable and optically clear. Melt-processable means that the composition is melt-processable, i.e., the composition can be heated and made to flow without causing decomposition. Melt-processable does not mean that the composition has been melt-processed, nor does it in any way indicate a processing step.
[0055] A wide variety of (meth)acrylic polymers and copolymers are suitable for use in the nanocomposite blend compositions of the present disclosure. As mentioned above, the blends include at least two different (meth)acrylic polymers or copolymers. The (meth)acrylic polymers and copolymers include acrylic acid or methacrylic acid monomers. In some embodiments, the (meth)acrylic polymers include homopolymers of acrylic acid or methacrylic acid. In other embodiments, the (meth)acrylic polymers are copolymers of at least one (meth)acrylic monomer that is acid functional and at least one monomer that is a (meth)acrylate that is not acid functional. Additionally, the (meth)acrylic polymers can contain other non-(meth)acrylate monomers that are copolymerizable with the (meth)acrylic and (meth)acrylate monomers. The copolymers can be formed by polymerization or copolymerization using free radical polymerization techniques. In some embodiments, the at least one (meth)acrylic polymer includes a copolymer that contains (meth)acrylic acid and at least one comonomer. A wide variety of comonomers are suitable. Suitable comonomers include ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide.
[0056] In some embodiments, the (meth)acrylic polymer comprises a copolymer of acrylic acid or methacrylic acid and at least an additional monomer. Typically, the (meth)acrylic acid monomer is present in an amount of 14% by weight or more. Typically, the difference in the (meth)acrylic acid monomer of the (meth)acrylic copolymer in the nanocomposite blend is 6% by weight or less. In some embodiments, the at least one additional monomer is ethylene, propylene, or a combination of ethylene and propylene. In other embodiments, the (meth)acrylic polymer comprises a copolymer of acrylic acid or methacrylic acid, ethylene, propylene, or a combination of ethylene and propylene, and at least one third monomer. Typically, the third monomer comprises an alkyl (meth)acrylate monomer. Examples of suitable alkyl (meth)acrylate monomers include n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate.
[0057] A wide range of blends of (meth)acrylic polymers or copolymers are suitable. Examples of suitable blends include blends of acrylic acid or methacrylic acid homopolymers and copolymers of acrylic acid or methacrylic acid and at least one additional monomer. Other examples include blends of acrylic acid or methacrylic acid homopolymers and copolymers of acrylic acid or methacrylic acid and at least two additional monomers. In some embodiments, the blends include copolymers of acrylic acid or methacrylic acid and at least one additional monomer and different copolymers of acrylic acid or methacrylic acid and at least one additional monomer. Still other embodiments include blends of copolymers of acrylic acid or methacrylic acid and at least one additional monomer and copolymers of acrylic acid or methacrylic acid and at least two additional monomers. In addition, the blends may also include different copolymers of acrylic acid or methacrylic acid and at least two additional monomers.
[0058] In some embodiments, the difference in (meth)acrylic acid monomer content in the first and second copolymers is less than 6% by weight. Similarity in monomer content aids in polymer compatibility.
[0059] In some embodiments, the (meth)acrylic polymer or copolymer is at least partially neutralized. This means that the protons of the carboxylic acid groups are replaced with cations, typically metal cations. Monovalent, divalent and higher valent cations are suitable. Examples of suitable cations include sodium cation, calcium cation, potassium cation, zinc cation, lithium cation, magnesium cation and aluminum cation. A combination of cations can also be used.
[0060] Suitable ethylene (meth)acrylic acid copolymers include PRIMACOR 5980i, EIdu from Dow Chemical Company (Midland, MI). Suitable aqueous dispersions of partially neutralized ethylene (meth)acrylic acid copolymers can be obtained from commercial sources, such as NUCREL 960 from Pont de Nemours and Company (Wilmington, DE), ESCOR 5200 from Exxon-Mobil (Irving, TX), and AC-5180 from Honeywell (Morris Plains, NJ). Suitable aqueous dispersions of partially neutralized ethylene (meth)acrylic acid copolymers can be obtained from commercial sources, such as MICHEM PRIME 4990R from Michelman, Inc. (Cincinnati, OH). Suitable partially neutralized ethylene (meth)acrylic acid copolymers can be obtained from commercial sources, including, for example, SURLYN 1706, 1707, 7940, 9020, 9120, and PC-350, and HPF 1000 from EI du Pont de Nemours and Company (Wilmington, DE).
[0061] A wide variety of metal oxide nanoparticles are suitable. Examples of suitable metal oxide nanoparticles include silicon (silicon is considered to be a metalloid and therefore a list of metal oxides). Among the more preferred metal oxide nanoparticles are those of silicon, i.e., silica nanoparticles.
[0062] The size of such particles is selected to avoid significant visible light scattering. The surface-modified metal oxide nanoparticles can be particles having a primary particle size or associated particle size greater than 1 nm (nanometer) and less than 200 nm (e.g., unassociated). In some embodiments, the particle size is greater than 4 nm, greater than 5 nm, greater than 10 nm, or greater than 20 nm. In some embodiments, the particle size is less than 190 nm, less than 150 nm, less than 100 nm, less than 75 nm, or less than 50 nm. Typically, the nanoparticles have a size in the range of 4-190 nm, 4-100 nm, 4-75 nm, 10-50 nm, or 20-50 nm. It is desirable for the nanoparticles to be unassociated. Particle size can be measured in a wide variety of ways, such as by transmission electron microscopy (TEM). Typically, commercially available metal oxide nanoparticles are supplied in the listed particle sizes or particle size ranges.
[0063] The nanoparticles are surface modified to improve compatibility with the polymer matrix material and to maintain the nanoparticles non-associated, non-weakly aggregated, non-strongly aggregated, or a combination thereof. The surface modification used to produce the surface-modified nanoparticles includes at least one acid-functional silane surface modifier. The acid-functional silane surface modifier has the general formula 1: [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10 Alkyl groups and C1-C 10The group A is selected from the group consisting of C1-C alkoxy groups. 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 The linker group is selected from the group consisting of amide-containing groups, such as -(CH2) a -NH-(CO)-(CH2) b -type groups, where a and b are integers equal to or greater than 1, and (CO) is a carbonyl group, C=O. In some embodiments, A is an alkylene group having 1 to 3 carbon atoms.
[0064] While acid-functional silanes may be commercially available, one aspect of the present disclosure involves the synthesis of carboxylic acid-functional silanes of Formula 1. In addition to the synthetic scheme shown below, acid-functional silane surface modifiers can be prepared using anhydride-functional silanes such as (3-triethoxysilyl)propylsuccinic anhydride, which can be obtained from commercial sources such as Gelest, Inc. (Morrisville, PA).
[0065] In one embodiment of the present disclosure, a solution is prepared from an organic acid anhydride dissolved in a first organic solvent. A second solution is prepared from an aminosilane in a second organic solvent. The two solutions are combined. The combined solution is continuously stirred at a suitable temperature and duration to synthesize a carboxylic acid functional silane of formula 1. In another embodiment, a solution is prepared from an organic acid anhydride dissolved in an organic solvent. The aminosilane is dissolved in the organic acid anhydride solution. The solution containing the organic acid anhydride and the aminosilane is continuously stirred at a suitable temperature and duration to synthesize a carboxylic acid silane of formula 1. The first and second organic solvents can be the same or different. When the first and second organic solvents are different, the first and second organic solvents are miscible. Both the first and second organic solvents are miscible with water.
[0066] Suitable organic acid anhydrides include succinic anhydride (3,4-dihydrofuran-2,5-dione), tetrahydrofuran-2,5-dione, 3-alkyltetrahydrofuran-2,5-diones such as 3-methyltetrahydrofuran-2,5-dione and 3-ethyltetrahydrofuran-2,5-dione, tetrahydropyran-2,6-dione, 3-alkyltetrahydropyran-2,6-diones such as 3-methyltetrahydropyran-2,6-dione and 3-ethyltetrahydropyran-2,6-dione, 4-alkyltetrahydropyran-2,6-diones such as 4-methyltetrahydropyran-2,6-dione, 4-ethyltetrahydropyran-2,6-dione, and 4,4'-methyltetrahydropyran-2,6-dione, oxepane-2,7-dione. Suitable organic acid anhydrides can be obtained from commercial sources such as Alfa Aesar (Ward Hill, Mass.) and Millipore Sigma (Burlington, Mass.). Succinic anhydride is a particularly suitable organic acid anhydride.
[0067] Suitable aminosilanes include aminopropyltrimethoxysilane, aminopropyltriethoxysilane, p-aminophenyltrimethoxysilane, p-aminophenyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, N-phenylaminopropyltriethoxysilane, n-butylaminopropyltrimethoxysilane, n-butylaminopropyltriethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, and (N,N-diethyl-3-aminopropyl)triethoxysilane.Suitable aminosilanes can be obtained from commercial sources such as Gelest, Inc. (Morrisville, PA), Alfa Aesar (Ward Hill, MA), Millipore Sigma (Burlington, MA), and Momentive Performance Materials (Waterford, NY).A particularly suitable aminosilane is aminopropyltrimethoxysilane.
[0068] A wide variety of organic solvents can be used. Suitable organic solvents include N,N-dimethylformamide (DMF), which can be obtained from commercial sources such as OmniSolv (Billerica, Mass.).
[0069] The surface-modified metal oxide nanoparticles are prepared by combining an aqueous nanodispersion of surface-unmodified metal oxide nanoparticles at a basic pH with a carboxylic acid functional silane surface modifier and reacting the carboxylic acid functional silane surface modifier with the metal oxide nanoparticle surface to result in an aqueous nanodispersion of surface-modified metal oxide nanoparticles, the nanoparticles being surface-modified with a carboxylic acid. This may be done in a variety of ways. In some embodiments, the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles is combined with a solution of a carboxylic acid silane of Formula 1 in an organic solvent. In other embodiments, the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles is combined with a base and a solution of a carboxylic acid silane of Formula 1 in an organic solvent. In other embodiments, the aqueous nanodispersion of surface-unmodified metal oxide nanoparticles is combined with a carboxylic acid silane of Formula 1. Generally, the carboxylic acid silane of Formula 1 is added in a concentration sufficient to modify 10-100% of the total metal oxide nanoparticle surface area in the nanodispersion. As discussed above, the metal oxide nanoparticles may have a variety of sizes. Typically, the average particle size is greater than 1 nm and less than 200 nm. In some embodiments, the particle size is greater than 4 nm, greater than 5 nm, greater than 10 nm, or greater than 20 nm. In some embodiments, the particle size is less than 190 nm, less than 150 nm, less than 100 nm, less than 75 nm, or less than 50 nm. Typically, the nanoparticles have a size in the range of 4-190 nm, 4-100 nm, 4-75 nm, 10-50 nm, or 20-50 nm. The surface-unmodified metal oxide nanoparticles can be dispersed in an aqueous solution having a pH in the range of 8-12. In some cases, since the addition of the carboxylic acid silane solution of Formula 1 tends to lower the pH, a base may be added to the aqueous nanodispersion of the surface-unmodified metal oxide nanoparticles to maintain the pH in the desired range. In some cases, the organic solvent is removed from the solution of the carboxylic acid silane in the organic solvent before combining the carboxylic acid silane with the aqueous nanodispersion of the surface-unmodified metal oxide nanoparticles.
[0070] An aqueous nano-dispersion of unmodified metal oxide nanoparticles may be prepared, or in some embodiments, an aqueous nano-dispersion of unmodified metal oxide nanoparticles may be obtained commercially. Suitable surface-unmodified metal oxide nanoparticles include aqueous nanodispersions commercially available from Nalco Chemical Company (Naperville, IL) under the trade designation "Nalco Colloidal Silicas", such as products NALCO 2326, 1130, DVSZN002, 1142, 2327, 1050, DVSZN004, 1060, and 2329K; from Nissan Chemical America Corporation (Houston, TX) under the trade designation SNOWTEX, such as products ST-NXS, ST-XS, ST-S, ST-30, ST-40, ST-N40, ST-50, ST-XL, and ST-YL; and from Nyacol Nano Technologies, Inc. (Ashland, MA) under the trade designation NEXSIL 5, 6, 12, 20, 85-40, 20A, 20K-30, and 20NH4.
[0071] Suitable bases include ammonium hydroxide, which can be obtained from commercial sources such as Millipore Sigma (Burlington, Mass.).
[0072] Typically, the surface-modified metal oxide nanoparticles are used as a nanodispersion and the particles are not isolated. Another aspect of the present disclosure involves the preparation of a nanodispersion of surface-modified metal oxide nanoparticles without precipitation, gelation, weak aggregation, or strong aggregation, wherein the metal oxide nanoparticles are surface-modified with a carboxylic acid silane of formula 1.
[0073] In some embodiments, the aqueous nano-dispersion of surface-unmodified metal oxide nanoparticles and a solution of the carboxylic acid silane of formula 1 in an organic solvent are combined in a reactor and heated at a suitable temperature and duration to react the carboxylic acid silane of formula 1 with the surface of the metal oxide nanoparticles. In other embodiments, the aqueous nano-dispersion of surface-unmodified metal oxide nanoparticles, a base, and a solution of the carboxylic acid silane of formula 1 in an organic solvent are combined in a reactor and heated at a suitable temperature and duration to react the carboxylic acid silane of formula 1 with the surface of the metal oxide nanoparticles. In some embodiments, a solvent exchange is performed on the aqueous nano-dispersion of the surface-modified metal oxide nanoparticles and the organic solvent to remove the organic solvent. In some embodiments, the reactor is open under reflux conditions, in other embodiments, the reactor is closed and under pressure. In some embodiments, the reactor is glass, and in some embodiments, the reactor is stainless steel.
[0074] A wide range of loadings of surface-modified metal oxide nanoparticles are suitable in the nanocomposite blend composition. Typically, the nanocomposite comprises at least 1 wt. % surface-modified metal oxide nanoparticles and up to 70 wt. % surface-modified metal oxide nanoparticles. In some embodiments, the surface-modified metal oxide nanoparticle concentration comprises 5-60 wt. %, or 10-50 wt. %.
[0075] Additional additives may include flame retardants, heat stabilizers, anti-slip agents, neutralizing agents, UV absorbers, light stabilizers, antioxidants, crosslinking agents, release agents, catalysts, colorants, antistatic agents, defoamers, plasticizers, and other processing aids.
[0076] Nanocomposite blends can include a wide range of configurations and articles. In some embodiments, nanocomposite blends can be configured into continuous or non-continuous articles. For example, nanocomposite blends can be in the form of films, sheets, filaments, particles, pellets, flakes, and the like. Additionally, an advantage of nanocomposite blends is that they can be configured into molded articles. Molding is a process commonly used in the plastics technology field and includes molding techniques such as rotational molding, injection molding, blow molding, compression molding, and vacuum molding. Using molding techniques, nanocomposite blends can be formed into a wide range of three-dimensional shapes. As mentioned above, the ability to form nanocomposite blends into three-dimensional shapes is something that is not possible with more rigid materials such as glass.
[0077] Also disclosed herein is a wide range of articles. Typically, the articles are optical articles. In some embodiments, the optical articles are optical film articles. In other embodiments, the articles are optical articles, including display devices and optical film articles. In other embodiments, the articles are optical articles, including photovoltaic devices and optical film articles.
[0078] An optical film article is an article that comprises an optical film. This means that the article may be an optical film or may include an optical film with other elements. In some embodiments, the optical film article comprises at least one layer of a polymer nanocomposite blend, the polymer nanocomposite blend comprising at least two (meth)acrylic polymers or copolymers composed of monomers selected from the group consisting of methacrylic acid and acrylic acid, and surface-modified metal oxide nanoparticles. Typically, the (meth)acrylic polymers or copolymers are miscible and at least partially neutralized. The surface-modified metal oxide nanoparticles are represented by the formula 1: [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10Alkyl groups and C1-C 10 The surface is modified with a surface modifier comprising a carboxylic acid silane of the group A selected from the group consisting of C1-C alkoxy groups. 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 The linker group is selected from the group consisting of amide-containing groups, such as -(CH2) a -NH-(CO)-(CH2) b -type groups, where a and b are integers equal to or greater than 1, and (CO) is a carbonyl group, C=O. In some embodiments, A is an alkylene group having 1 to 3 carbon atoms. These nanocomposite blends are discussed in detail above.
[0079] The optical film article has a wide range of desirable properties. The optical film article is flexible, bendable, rollable, and / or foldable. These properties can be measured in a variety of ways, as will be appreciated by those skilled in the art. In some embodiments, the optical film article is formable into a variety of three-dimensional shapes. In addition to the mechanical properties listed above, the optical film article also has desirable optical properties. In general, the optical film article is optically transparent and may be optically clear. Typically, an optically clear optical film article has a luminous transmittance in the visible light spectrum (about 400 to about 700 nm) of at least 80% and a haze value of 10% or less. In some embodiments, the optical film article has a luminous transmittance in the visible light spectrum (about 400 to about 700 nm) of greater than 85%, greater than 87%, greater than 89%, or greater than 90%. In some embodiments, the optical film article has a haze value of less than 7%, less than 5%, less than 4%, or even less than 3%. Luminous transmittance and haze can be measured using the techniques described in the Examples section.
[0080] In some embodiments, the optical film article is nominally colorless. As noted above, this is* In some embodiments, the yellowness index b is less than 5. * The value is 4 or less, 3 or less, 2 or less, or even 1 or less.
[0081] In some embodiments, the optical film article is a multilayer optical film article. This means that in addition to at least one nanocomposite blend layer, there is at least one additional layer in the optical film article. A wide variety of additional layers are suitable for use in the multilayer optical film article of the present disclosure. The additional layer(s) may be a coating, a laminate, or a coextrusion layer. Examples of suitable layers include permanent layers and removable layers. A permanent layer is one that remains in the multilayer optical film article when the multilayer optical film article is used, while a removable layer is one that is removed before the multilayer optical film article is used.
[0082] Examples of suitable permanent layers include transparent functional coating layers and transparent adhesive layers.A wide range of transparent functional coatings are suitable depending on the desired properties of the optical film article.Examples of suitable transparent functional coating layers include hard coat layers, ultraviolet (UV) protective layers, conductive layers, barrier layers, microstructure layers, anti-glare layers, anti-reflection layers, anti-fingerprint layers, or anti-sparkle layers.Such layers are well known and understood in the art.
[0083] Examples of suitable transparent adhesive layers include transparent pressure-sensitive adhesive layers and transparent heat-activated adhesives. A wide range of suitable transparent pressure-sensitive adhesives are known, including (meth)acrylate adhesives, block copolymer adhesives, silicone adhesives, and the like. Examples of transparent heat-activated adhesives include polyvinyl butyral (PVB). Examples of suitable adhesives include, for example, 3M OPTICALLY CLEAR ADHESIVES and 3M CONTRAST ENHANCEMENT FILMS.
[0084] Examples of removable layers include handling films and release liners that can be applied to a multilayer optical film article to protect the surface of the article during shipping and handling of the article, and are removed prior to use of the article.
[0085] Also disclosed is an optical article comprising a display device and an optical film article in contact with a surface of the display device. The optical film article is described above and includes at least one layer of the nanocomposite blend composition and may be a multi-layer film article.
[0086] A wide variety of display devices are suitable for the optical articles of the present disclosure. The display device may include a display window. The display device may be any useful article, such as a phone or smartphone, an electronic tablet, an electronic organizer, a computer, etc. Optical displays include organic light-emitting diode (OLED) display panels. Optical displays include liquid crystal display (LCD) panels or reflective displays. Examples of reflective displays include electrophoretic displays, electrofluidic displays (such as electrowetting displays), interference displays or electronic paper display panels, which are described in US Patent Publication No. 2015 / 0330597. Further examples of optical displays include static displays, such as commercial graphic displays and billboards.
[0087] A wide variety of articles of the present disclosure are suitable protective layers for photovoltaic devices, such as encapsulation layers for photovoltaic solar panels.
[0088] In some embodiments, the optical article comprises a display device having a molded optical film article, where the molded optical film article is a molded optical film article.
[0089] Methods of making optical articles are also disclosed herein. In some embodiments, the methods of making optical articles include preparing a nanocomposite blend, the nanocomposite blend comprising the steps of: (a) preparing an aqueous nano-dispersion of surface-modified metal oxide nanoparticles, where the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of a first (meth)acrylic polymer or copolymer, where the (meth)acrylic polymer or copolymer has been at least partially neutralized; and (c) combining the dispersions of (a) and (b) to obtain the surface-modified metal oxide nanoparticles and the nanocomposite blend. (d) forming an aqueous nano-dispersion of (c) and a first (meth)acrylic polymer or copolymer, (d) drying and / or concentrating the nano-dispersion of (c), and (e) melt processing a second (meth)acrylic polymer or copolymer with the dried and / or concentrated nano-dispersion (d) to form a nanocomposite blend of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer, wherein the surface of the metal oxide nanoparticles has been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer has been at least partially neutralized. The (meth)acrylic polymer or copolymer and the surface-modified metal oxide nanoparticles are discussed in detail above.
[0090] In some embodiments, the (meth)acrylic polymer or copolymer added during melt processing is at least partially neutralized, as is the case for ionomers. In some embodiments, the (meth)acrylic polymer or copolymer added during melt processing is not neutralized. In some embodiments, an additional neutralizing agent is added during melt processing. Additional neutralizing agents suitable for addition during melt processing include metal salts of oxides, hydroxides, acetates, and stearates of zinc, magnesium, sodium, lithium, calcium, potassium, and aluminum.
[0091] In some embodiments, a method for preparing a nanocomposite blend includes the steps of: (a) preparing an aqueous nanodispersion of surface-modified metal oxide nanoparticles, wherein the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of at least two (meth)acrylic polymers or copolymers, wherein the (meth)acrylic polymers or copolymers have been at least partially neutralized; (c) combining the dispersions of (a) and (b) to form an aqueous nanodispersion of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer; (d) drying and / or concentrating the nanodispersion of (c); and (e) melt processing the dried and / or concentrated nanodispersion (d) to form a nanocomposite blend of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer, wherein the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer have been at least partially neutralized. The (meth)acrylic polymer or copolymer and the surface-modified metal oxide nanoparticles are discussed in detail above.
[0092] In some embodiments, the nanodispersion is dried, meaning that essentially all water and / or organic solvent is removed, in other embodiments, the nanodispersion is concentrated, meaning that a portion of the water and / or organic solvent is removed, and in some embodiments, a combination of concentration and drying is performed, for example, concentration by one method and drying by a different method. In some embodiments, drying is performed by a suitable method such as evaporative drying, thermal drying, or spray drying. Suitable concentration methods include deposition methods such as the use of falling film evaporators or thin film evaporators, tangential flow filtration, and precipitation by adding a precipitating agent. Methods such as precipitation can be followed by separation methods such as decantation, pressing, filtration, or centrifugation.
[0093] In some embodiments, melt processing is carried out by an extruder, mixer, kneader, or compounder. Suitable melt processing operations are available from commercial sources such as Leitritz Advanced Technologies Corporation (Somerville, NJ), Krauss-Maffei Bertsdorff (Florence, KY), CW Brabender Instruments Incorporated (South Hackensack, NJ), Farrell Corporation (Ansonia, CT), LIST Technology AG (Arisdorf, Switzerland), and Buss USA (Carol Stream, IL).
[0094] In some embodiments, the formed nanocomposite blend comprises an optical film. Optical films are discussed in detail above. As noted above, the optical film article may be monolithic (i.e., may include only the nanocomposite blend) or may be a multi-layer optical film article. Additionally, the formed nanocomposite blend may be in a variety of three-dimensional shapes.
[0095] The nanocomposite blend articles and devices of the present disclosure are further illustrated in the figures.
[0096] 1 is a schematic side view of an exemplary flexible display film article 30. The article 30 includes a flexible display film 10 that includes a transparent elastomeric nanocomposite blend layer 14.
[0097] The flexible display film 10 may have a haze value of 10% or less. In some embodiments, the flexible display film 10 may have a haze value of 5% or less, 4% or less, or 3% or less. The flexible display film 10 may have a transparency of 95% or more, or 97% or more. The flexible display film 10 may have a visible light transmittance of 85% or more, or 90% or more, or 93% or more.
[0098] The flexible display film 10 may be nominally colorless and have a yellowness index or b of 5 or less, or 4 or less, or 3 or less, or 2 or less, or 1 or less. * In many embodiments, the display film 10 has a yellowness index or b value of 1 or less. * The value may be:
[0099] After at least 100,000 bending or folding cycles of about 3 millimeter (mm) radius, the flexible display film 10 can maintain a haze value of 5% or less. After at least 100,000 bending or folding cycles of about 5 mm radius, or about 4 mm radius, or about 3 mm radius, or about 2 mm radius, or about 1 mm radius, the flexible display film 10 can maintain a stable haze value or remain intact without cracking or delamination. After at least 100,000 bending or folding cycles of about 3 mm radius or less, the flexible display film 10 can remain intact.
[0100] The flexible display film 10 can have any useful thickness. In many embodiments, the flexible display film 10 has a thickness of 500 micrometers or less, or 400 micrometers or less, or 300 micrometers or less, or 200 micrometers or less. The thickness of the flexible display film 10 is a balance between being thick enough to provide the desired display protection and being thin enough to accommodate folding and thinning design parameters.
[0101] 2 is a schematic side view of an exemplary flexible display film article 31. Article 31 includes a flexible display film 10 that includes a transparent elastomeric nanocomposite blend layer 14 and a transparent functional coating layer 15.
[0102] The transparent functional coating layer 15 may be an abrasion resistant hard coat, or a conductive layer for a touch sensitive display element, or a barrier layer to reduce or retard the ingress of oxygen or water through the flexible display film 10. The transparent barrier layer may include, for example, alternating thin layers of silica, alumina or zirconia and an organic resin. Exemplary transparent barrier layers are described in U.S. Patent No. 7,980,910 and PCT Publication No. WO 2003 / 094256.
[0103] Other transparent functional coating layers 15 include a microstructure layer, a slip agent layer, an anti-glare layer, an anti-reflection layer, or an anti-fingerprint layer. Additional transparent functional coating layers 15 may be disposed inside the display film. One useful transparent functional coating layer 15 disposed in the flexible display film 10 is a sparkle reduction layer, as described in PCT Publication No. WO2015 / 191949. Sparkle reduction layers may be particularly useful in high definition displays that include anti-glare coatings.
[0104] 3 is a schematic side view of an exemplary flexible display film article 32. Article 32 comprises a flexible display film 10 including a transparent elastomeric nanocomposite blend layer 14 and a transparent functional coating layer 15, with removable liners 22 and 27 providing shipping protection to the underlying flexible display film 10.
[0105] 4 is a schematic side view of an exemplary flexible display film article 33. Article 33 comprises a flexible display film 10 including a transparent elastomeric nanocomposite blend layer 14, a transparent functional coating layer 15, and a transparent adhesive layer 24, with removable liners 22 and 27 providing shipping protection to the underlying flexible display film 10.
[0106] 5 is a schematic side view of an exemplary flexible display film 10 on an optical element 26 forming an article 40. The flexible display film 10 includes a transparent elastomeric nanocomposite blend layer 14. A transparent adhesive layer 24 adheres the flexible display film 10 to the optical element 26. In some cases, the transparent adhesive layer 24 permanently secures the flexible display film 10 to the optical element 26. In some cases, the flexible display film 10 and adhesive layer 24 can be removed / peeled / repositioned against the optical element 26 by application of heat or mechanical force such that the flexible display film is replaceable or repositionable by a consumer.
[0107] 6 is a schematic side view of an exemplary flexible display film 10 on an optical element 26 forming an article 41. The flexible display film 10 includes a transparent elastomeric nanocomposite blend layer 14 and a transparent functional coating layer 15. A transparent adhesive layer 24 adheres the flexible display film 10 to the optical element 26. In some cases, the transparent adhesive layer 24 permanently secures the flexible display film 10 to the optical element 26. In some cases, the flexible display film 10 and adhesive layer 24 can be removed / peeled / repositioned against the optical element 26 by application of heat or mechanical force such that the flexible display film is replaceable or repositionable by a consumer.
[0108] 7 is a schematic perspective view of an exemplary foldable display device 70 including an exemplary flexible display film 10. The flexible display film 10 can be any of the display film structures described herein disposed over an optical element, such as an optical display 74. The display device 70 may not be a folding article, may bend only within a certain range, or may be a static curved display device.
[0109] The optical display 74 may form at least a portion of a display device. The display device 70 may include a display window 72. The display device 70 may be any useful article, such as a phone or smartphone, an electronic tablet, an electronic organizer, a computer, etc. Optical displays include organic light-emitting diode (OLED) display panels. Optical displays include liquid crystal display (LCD) panels or reflective displays. Examples of reflective displays include electrophoretic displays, electrofluidic displays (such as electrowetting displays), interferometric displays or electronic paper display panels, which are described in U.S. Patent Publication No. 2015 / 0330597. Further examples of optical displays include static displays, such as commercial graphic displays and billboards.
[0110] The flexible display film 10 and the optical display 74 can be foldable such that the optical display 74 faces itself and at least a portion of the display film 10 contacts or directly faces another portion of the flexible display film 10, as shown in Figure 7. The flexible display film 10 and the optical display 74 can be flexible or bendable or rollable or foldable such that a portion of the display film 10 and the optical display 74 can be bonded to another portion of the flexible display film 10 and the optical display 74. The display film 10 and the optical display 74 can be flexible or bendable or rollable or foldable such that a portion of the flexible display film 10 and the optical display 74 can be bonded at least 90 degrees or at least 170 degrees to another portion of the display film 10 and the optical display 74.
[0111] The flexible display film 10 and the optical display 74 can be flexible or bendable or rollable or foldable such that a portion of the display film 10 and the optical display 74 can be bonded to another portion of the flexible display film 10 and the optical display 74, forming a bend radius of 3 mm or less at a bend or fold line in the display film 10. The flexible display film 10 and the optical display 74 can be flexible or bendable or rollable or foldable such that a portion of the flexible display film 10 and the optical display 74 can be bonded to another portion of the display film 10 and the optical display 74, forming a bend radius such that the flexible display film 10 overlaps itself and is separated from each other by a distance of 10 mm or less, or 6 mm or less, or 3 mm or less, or touches each other. Although FIG. 7 shows the display device 74 folded inwardly and the surfaces of the display film 10 approach each other, there are other cases in which the display device can be folded in the opposite direction or outward (outfold) such that the flexible display film 10 is on the outer surface of the display device.
[0112] The present disclosure includes the following embodiments.
[0113] Among the embodiments are nanocomposite blends. Embodiment 1 includes a first (meth)acrylic polymer or copolymer comprised of a monomer selected from the group consisting of methacrylic acid and acrylic acid, a second (meth)acrylic polymer or copolymer comprised of a monomer selected from the group consisting of methacrylic acid and acrylic acid, and a (meth)acrylic polymer or copolymer represented by Formula 1. [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10 Alkyl groups and C1-C 10 A is selected from the group consisting of C1-C10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 and surface-modified metal oxide nanoparticles that have been surface-modified with a surface modifier comprising a carboxylic acid silane, wherein the linker group is selected from the group consisting of amide-containing groups.
[0114] Embodiment 2 is a nanocomposite blend as described in embodiment 1, wherein at least one of the first and second (meth)acrylic polymers or copolymers comprises a copolymer comprising at least one additional monomer selected from the group consisting of ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide.
[0115] Embodiment 3 is the nanocomposite blend of embodiment 3, wherein the at least one additional monomer comprises ethylene, propylene, or a combination thereof.
[0116] Embodiment 4 is a nanocomposite blend of any one of embodiments 1-3, wherein the first and second (meth)acrylic polymers or copolymers are at least partially neutralized with sodium cations, calcium cations, potassium cations, zinc cations, lithium cations, magnesium cations, aluminum cations, or combinations thereof.
[0117] Embodiment 5 is a nanocomposite blend according to any one of embodiments 2-4, wherein the (meth)acrylic monomer is present in an amount of at least 14% by weight.
[0118] Embodiment 6 is the nanocomposite blend of embodiment 5, wherein the difference in the (meth)acrylic acid monomer in the first and second copolymers is less than 6% by weight.
[0119] Embodiment 7 is the nanocomposite blend of any one of embodiments 2-6, wherein the additional monomer comprises ethylene or propylene.
[0120] Embodiment 8 is the nanocomposite blend of embodiment 7, wherein at least one of the first and second (meth)acrylic copolymers further comprises at least one third monomer selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate.
[0121] Embodiment 9 is a nanocomposite blend according to any one of embodiments 1 to 8, wherein the concentration of the surface-modified metal oxide nanoparticles is from 1 to 70% by weight.
[0122] Embodiment 10 is a nanocomposite blend according to any one of embodiments 1 to 8, wherein the concentration of the surface-modified metal oxide nanoparticles is from 5 to 60% by weight.
[0123] Embodiment 11 is a nanocomposite blend according to any one of embodiments 1 to 8, wherein the concentration of the surface-modified metal oxide nanoparticles is 10 to 50 weight percent.
[0124] Embodiment 12 is a nanocomposite blend according to any one of embodiments 1 to 11, wherein the surface-modified metal oxide nanoparticles have an average diameter between 1 nanometer and 200 nanometers.
[0125] Embodiment 13 is a nanocomposite blend according to any one of embodiments 1 to 11, wherein the surface-modified metal oxide nanoparticles have an average diameter between 4 nanometers and 190 nanometers.
[0126] Embodiment 14 is a nanocomposite blend according to any one of embodiments 1 to 11, wherein the surface-modified metal oxide nanoparticles have an average diameter between 4 nanometers and 100 nanometers.
[0127] Embodiment 15 is a nanocomposite blend according to any one of embodiments 1 to 11, wherein the surface-modified metal oxide nanoparticles have an average diameter between 4 nanometers and 75 nanometers.
[0128] Embodiment 16 is a nanocomposite blend according to any one of embodiments 1 to 11, wherein the surface-modified metal oxide nanoparticles have an average diameter between 10 nanometers and 50 nanometers.
[0129] Embodiment 17 is a nanocomposite blend according to any one of embodiments 1 to 11, wherein the surface-modified metal oxide nanoparticles have an average diameter between 20 nanometers and 50 nanometers.
[0130] Embodiment 18 is a nanocomposite blend according to any one of embodiments 1 to 17, wherein the surface-modified metal oxide nanoparticles comprise surface-modified nanoparticles of a metal oxide of silicon, titanium, aluminum, hafnium, zinc, tin, cerium, yttrium, indium, antimony, or mixtures thereof.
[0131] Embodiment 19 is the nanocomposite blend of embodiment 18, wherein the surface-modified metal oxide nanoparticles comprise surface-modified silica particles.
[0132] Embodiment 20 is a nanocomposite blend according to any one of embodiments 1 to 19, wherein the carboxylic acid silane is produced by the reaction of an organic acid anhydride with an aminoalkyltrialkoxysilane.
[0133] Embodiment 21 is the nanocomposite blend of embodiment 20, wherein the organic acid silane is succinic anhydride.
[0134] Embodiment 22 is the nanocomposite blend of embodiment 20, wherein the aminoalkyltrialkoxysilane is 3-aminopropyltrimethoxysilane.
[0135] Embodiment 23 is a nanocomposite blend according to any one of embodiments 1 to 22, wherein the nanocomposite comprises an article in the form of a film, sheet, filament, particle, pellet, flake, or molded article.
[0136] Also disclosed is an optical film article. Embodiment 24 is an optical film article comprising at least one layer of a polymer nanocomposite blend, the polymer nanocomposite blend comprising a first (meth)acrylic polymer or copolymer comprised of a monomer selected from the group consisting of methacrylic acid and acrylic acid, a second (meth)acrylic polymer or copolymer comprised of a monomer selected from the group consisting of methacrylic acid and acrylic acid, and a compound represented by Formula 1. [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10 Alkyl groups and C1-C 10 A is selected from the group consisting of C1-C 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 and a surface-modified metal oxide nanoparticle that has been surface-modified with a surface modifier comprising a carboxylic acid silane, wherein the linker group is selected from the group consisting of amide-containing groups.
[0137] Embodiment 25 is the optical film article of embodiment 24, wherein the optical film article is flexible, bendable, rollable, foldable, or formable.
[0138] Embodiment 26 is the optical film article of embodiment 24 or 25, wherein at least one of the first and second (meth)acrylic polymers or copolymers comprises a copolymer comprising at least one additional monomer selected from the group consisting of ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide.
[0139] Embodiment 27 is the optical film article of embodiment 26, wherein the at least one additional monomer comprises ethylene, propylene, or a combination thereof.
[0140] Embodiment 28 is the optical film article of any one of embodiments 24-27, wherein the (meth)acrylic polymer is at least partially neutralized with sodium cations, calcium cations, potassium cations, zinc cations, lithium cations, magnesium cations, aluminum cations, or combinations thereof.
[0141] Embodiment 29 is the optical film article of any one of embodiments 26-28, wherein the (meth)acrylic monomer is present in an amount of at least 14 weight percent.
[0142] Embodiment 30 is the optical film article of embodiment 29, wherein the difference in the (meth)acrylic acid monomer in the first and second copolymers is less than 6% by weight.
[0143] Embodiment 31 is the optical film article of any one of embodiments 26-30, wherein the additional monomer comprises ethylene or propylene.
[0144] Embodiment 32 is the optical film article of embodiment 31, wherein at least one of the first and second (meth)acrylic copolymers further comprises at least one third monomer selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate.
[0145] Embodiment 33 is the optical film article of any one of embodiments 24-32, wherein a concentration of the surface-modified metal oxide nanoparticles is from 1 to 70 weight percent.
[0146] Embodiment 34 is the optical film article of any one of embodiments 24-32, wherein a concentration of the surface-modified metal oxide nanoparticles is from 5 to 60 weight percent.
[0147] Embodiment 35 is the optical film article of any one of embodiments 24-32, wherein a concentration of the surface-modified metal oxide nanoparticles is 10-50 weight percent.
[0148] Embodiment 36 is the optical film article of any one of embodiments 24-35, wherein the surface-modified metal oxide nanoparticles have an average diameter from 1 nanometer to 200 nanometers.
[0149] Embodiment 37 is the optical film article of any one of embodiments 24-35, wherein the surface-modified metal oxide nanoparticles have an average diameter from 4 nanometers to 190 nanometers.
[0150] Embodiment 38 is the optical film article of any one of embodiments 24-35, wherein the surface-modified metal oxide nanoparticles have an average diameter from 4 nanometers to 100 nanometers.
[0151] Embodiment 39 is the optical film article of any one of embodiments 24-35, wherein the surface-modified metal oxide nanoparticles have an average diameter from 4 nanometers to 75 nanometers.
[0152] Embodiment 40 is the optical film article of any one of embodiments 24-35, wherein the surface-modified metal oxide nanoparticles have an average diameter between 10 nanometers and 50 nanometers.
[0153] Embodiment 41 is the optical film article of any one of embodiments 24-35, wherein the surface-modified metal oxide nanoparticles have an average diameter between 20 nanometers and 50 nanometers.
[0154] Embodiment 42 is the optical film article of any one of embodiments 24-41, wherein the surface-modified metal oxide nanoparticles comprise surface-modified nanoparticles of a metal oxide of silicon, titanium, aluminum, hafnium, zinc, tin, cerium, yttrium, indium, antimony, or mixtures of metal oxides thereof.
[0155] Embodiment 43 is the optical film article of embodiment 42, wherein the surface-modified metal oxide nanoparticles comprise surface-modified silica particles.
[0156] Embodiment 44 is the optical film article of any one of embodiments 24-43, wherein the carboxylic acid silane is produced by reaction of an organic acid anhydride with an aminoalkyltrialkoxysilane.
[0157] Embodiment 45 is the optical film article of embodiment 44, wherein the organic acid silane is succinic anhydride.
[0158] Embodiment 46 is the optical film article of embodiment 44, wherein the aminoalkyltrialkoxysilane is 3-aminopropyltrimethoxysilane.
[0159] Embodiment 47 is the optical film article of any one of embodiments 24-46, wherein the optical film article is a multilayer optical film article.
[0160] Embodiment 48 is the optical film article of embodiment 47, wherein the multilayer optical film article further comprises at least one additional layer comprising a transparent functional coating layer, a transparent adhesive layer, and one or more removable layers.
[0161] Embodiment 49 is the optical film article of embodiment 48, wherein the transparent functional coating comprises a hardcoat layer, a conductive layer, a barrier layer, a microstructured layer, a slip agent layer, an antiglare layer, an antireflective layer, an antifingerprint layer, or an antisparkle layer.
[0162] Embodiment 50 is the optical film article of any one of embodiments 24-49, wherein the optical film article is optically clear.
[0163] Embodiment 51 is the optical film article of embodiment 50, wherein the optical film article is nominally colorless.
[0164] Embodiment 52 is the optical film article of embodiment 50 or 51, wherein the optical film article has a luminous transmission greater than 85% and a haze value less than 10%.
[0165] Optical articles are also disclosed herein. Embodiment 53 is an optical article comprising a display device and an optical film article in contact with a surface of the display device, the optical film article comprising a flexible, bendable, rollable, foldable, or formable optical film comprising at least one layer of a polymer nanocomposite blend, the polymer nanocomposite blend comprising a first (meth)acrylic polymer or copolymer comprised of a monomer selected from the group consisting of methacrylic acid and acrylic acid, a second (meth)acrylic polymer or copolymer comprised of a monomer selected from the group consisting of methacrylic acid and acrylic acid, and a compound represented by Formula 1. [ka] (Wherein, R1 is C1 to C 10 R2 and R3 are independently a C1-C 10 Alkyl groups and C1-C 10 A is selected from the group consisting of C1-C 10 Alkylene or arylene group, C1-C 10 Aralkylene group, C2-C 16 Heteroalkylene or heteroarylene groups, and C2-C 16 and a surface-modified metal oxide nanoparticle that has been surface-modified with a surface modifier comprising a carboxylic acid silane, wherein the linker group is selected from the group consisting of amide-containing groups.
[0166] Embodiment 54 is the optical article of embodiment 53, wherein the optical article comprises a display device having a molded optical film article, and the molded optical film article is a molded optical film article.
[0167] Embodiment 55 is the optical article of embodiment 53 or 54, wherein at least one of the first and second (meth)acrylic polymers or copolymers comprises a copolymer comprising at least one additional monomer selected from the group consisting of ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide.
[0168] Embodiment 56 is the optical article of embodiment 55, wherein the at least one additional monomer comprises ethylene, propylene, or a combination thereof.
[0169] Embodiment 57 is the optical article of any one of embodiments 53-56, wherein the (meth)acrylic polymer or copolymer is at least partially neutralized with sodium cations, calcium cations, potassium cations, zinc cations, lithium cations, magnesium cations, aluminum cations, or combinations thereof.
[0170] Embodiment 58 is the optical article of any one of embodiments 53-57, wherein the (meth)acrylic monomer is present in an amount of at least 14% by weight.
[0171] Embodiment 59 is the optical article of embodiment 58, wherein the difference in the (meth)acrylic acid monomer in the first and second copolymers is less than 6% by weight.
[0172] Embodiment 60 is the optical article of any one of embodiments 53-59, wherein the additional monomer comprises ethylene or propylene.
[0173] Embodiment 61 is the optical article of embodiment 60, wherein at least one of the (meth)acrylic copolymers further comprises at least one third monomer selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate.
[0174] Embodiment 62 is the optical article of any one of embodiments 53 to 61, wherein the concentration of the surface-modified metal oxide nanoparticles is 1 to 70 wt %.
[0175] Embodiment 63 is the optical article of any one of embodiments 53 to 61, wherein the concentration of the surface-modified metal oxide nanoparticles is 5 to 60 wt %.
[0176] Embodiment 64 is the optical article of any one of embodiments 53 to 61, wherein the concentration of the surface-modified metal oxide nanoparticles is 10 to 50 wt %.
[0177] Embodiment 65 is the optical article of any one of embodiments 53 to 64, wherein the surface-modified metal oxide nanoparticles have an average diameter from 1 nanometer to 200 nanometers.
[0178] Embodiment 66 is the optical article of any one of embodiments 53 to 64, wherein the surface-modified metal oxide nanoparticles have an average diameter from 4 nanometers to 190 nanometers.
[0179] Embodiment 67 is the optical article of any one of embodiments 53 to 64, wherein the surface-modified metal oxide nanoparticles have an average diameter from 4 nanometers to 100 nanometers.
[0180] Embodiment 68 is the optical article of any one of embodiments 53 to 64, wherein the surface-modified metal oxide nanoparticles have an average diameter from 4 nanometers to 75 nanometers.
[0181] Embodiment 69 is the optical article of any one of embodiments 53-64, wherein the surface-modified metal oxide nanoparticles have an average diameter of 10 nanometers to 50 nanometers.
[0182] Embodiment 70 is the optical article of any one of embodiments 53-64, wherein the surface-modified metal oxide nanoparticles have an average diameter between 20 nanometers and 50 nanometers.
[0183] Embodiment 71 is the optical article of any one of embodiments 53 to 70, wherein the surface-modified metal oxide nanoparticles comprise surface-modified nanoparticles of a metal oxide of silicon, titanium, aluminum, hafnium, zinc, tin, cerium, yttrium, indium, antimony, or mixtures thereof.
[0184] Embodiment 72 is the optical article of embodiment 71, wherein the surface-modified metal oxide nanoparticles comprise surface-modified silica particles.
[0185] Embodiment 73 is the optical article of any one of embodiments 53-72, wherein the carboxylic acid silane is produced by reaction of an organic acid anhydride with an aminoalkyltrialkoxysilane.
[0186] Embodiment 74 is the optical article of embodiment 73, wherein the organic acid silane is succinic anhydride.
[0187] Embodiment 75 is the optical article of embodiment 73, wherein the aminoalkyltrialkoxysilane is 3-aminopropyltrimethoxysilane.
[0188] Embodiment 76 is the optical article of any one of embodiments 53-75, wherein the optical film article is a multilayer optical film article.
[0189] Embodiment 77 is the optical article of embodiment 76, wherein the multilayer optical film article further comprises at least one additional layer comprising a transparent functional coating layer, a transparent adhesive layer, and one or more removable layers.
[0190] Embodiment 78 is the optical article of embodiment 77, wherein the transparent functional coating comprises a hard coat layer, a conductive layer, a barrier layer, a microstructured layer, a slip agent layer, an antiglare layer, an antireflective layer, an antifingerprint layer, or an antisparkle layer.
[0191] Embodiment 79 is the optical article of any one of embodiments 53-78, wherein the optical film article is optically clear.
[0192] Embodiment 80 is the optical article of embodiment 79, wherein the optical film article is nominally colorless.
[0193] Embodiment 81 is the optical article of embodiment 79 or 80, wherein the optical film article has a luminous transmittance of greater than 85% and a haze value of less than 10%.
[0194] Also disclosed is a method of making an optical article. Embodiment 82 is a method of making an optical article comprising preparing a nanocomposite blend, the nanocomposite blend comprising: (a) preparing an aqueous nanodispersion of surface-modified metal oxide nanoparticles, the surfaces of which are modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of at least two (meth)acrylic polymers or copolymers, the (meth)acrylic polymers or copolymers being at least partially neutralized; and (c) combining the dispersions of (a) and (b) to obtain a nanocomposite blend of the following formula: (d) forming an aqueous nano-dispersion of surface-modified metal oxide nanoparticles and a (meth)acrylic polymer or copolymer; (d) drying and / or concentrating the nano-dispersion of (c); and (e) melt processing the dried and / or concentrated nano-dispersion (d) to form a nanocomposite blend of the surface-modified metal oxide nanoparticles and the (meth)acrylic polymer or copolymer, wherein the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer have been at least partially neutralized.
[0195] The method of embodiment 82, wherein the formed nanocomposite blend comprises the optical film article of any one of embodiments 24 to 52.
[0196] 84. The method of embodiment 83, further comprising contacting the optical film article with a surface of the display article to form the optical article of any one of embodiments 53-81.
[0197] Embodiment 84 is a method of making an optical article comprising preparing a nanocomposite blend, the nanocomposite blend comprising: (a) preparing an aqueous nanodispersion of surface-modified metal oxide nanoparticles, where the metal oxide nanoparticles are surface-modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of a first (meth)acrylic polymer or copolymer, where the (meth)acrylic polymer or copolymer is at least partially neutralized; and (c) combining the dispersions of (a) and (b) to obtain a nanocomposite blend of the surface-modified metal oxide nanoparticles and the first (meth)acrylic polymer or copolymer. (d) forming an aqueous nano-dispersion of a meth)acrylic polymer or copolymer; (d) drying and / or concentrating the nano-dispersion of (c); and (e) melt processing the dried and / or concentrated nano-dispersion (d) and a second (meth)acrylic polymer or copolymer to form a nanocomposite blend of surface-modified metal oxide nanoparticles and a (meth)acrylic polymer or copolymer, wherein the surfaces of the metal oxide nanoparticles have been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer has been at least partially neutralized.
[0198] Embodiment 85 is the method of embodiment 84, wherein the formed nanocomposite blend comprises the optical film article of any one of embodiments 24 to 52.
[0199] Embodiment 86 is the method of embodiment 84, further comprising contacting the optical film article with a surface of the display article to form the optical article of any one of embodiments 53-81. EXAMPLES
[0200] The examples demonstrate nanocomposite blend compositions of surface modified metal oxide nanoparticles, namely silica, and (meth)acrylic acid copolymers.
[0201] [Table 1]
[0202] Preparation Example PE-1: Preparation of surface-modified silica nanoparticles Step 1A: Preparation of carboxylic acid silanes: 71 grams of N,N-dimethylformamide (DMF) was placed into an 8 ounce clear glass jar. A Teflon coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was started. 17.8 grams of succinic anhydride (SA) was added to the jar. The SA dissolved in the DMF within 10 minutes. 128 grams of DMF was placed into another 8 ounce clear glass jar. A Teflon coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was started. 32 grams of 3-aminopropyltrimethoxysilane (AMINO-TMOS) was added to the jar. The AMINO-TMOS dissolved immediately in the DMF. The SA / DMF solution was transferred to a 16 ounce clear glass jar. A Teflon coated stir bar was added to the jar, the jar was placed on a stir plate and stirring was started. The AMINO-TMOS / DMF solution was added slowly to the SA / DMF solution. The solution was stirred continuously at room temperature for 24 hours to complete the synthesis of carboxylic acid silanes, which was confirmed by NMR. Reaction Scheme 1 summarizes the reaction chemistry for synthesizing carboxylic acid silanes.
[0203] Step 1B: Preparation of carboxylic acid silanes: 2,500 grams of DMF was placed in a 4 liter brown glass jug. A Teflon coated stir bar was added to the jug, the jug was placed on a stir plate and stirring was started. 250 grams of SA was added to the jug dissolved in DMF. 400 grams of AMINO-TMOS was slowly added to the jug. The solution in the jug was stirred continuously at room temperature for 24 hours to complete the synthesis of the carboxylic acid silane, which was confirmed by NMR. [ka] Step 1C: Preparation of carboxylic acid modified silica nanoparticles: 400 grams of aqueous silica nanodispersion (ASN) was placed in a 32 ounce clear glass jar. The nanodispersion contained nominally 40 weight percent spherical surface unmodified silica nanoparticles with a nominal 20 nanometer diameter. A Teflon coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was started. 351.1 grams of deionized water (DIH2O) was slowly added to the jar. 123.6 grams of the carboxylic acid silane / DMF solution prepared as described in step 1A above was slowly added to the jar and stirring was continued for an additional 20 minutes. The stir bar was removed and the jar was sealed and placed in a preheated oven at 80°C for 24 hours to complete the carboxylic acid surface modification of the silica nanoparticles and form a nanodispersion of surface modified silica nanoparticles.
[0204] Step 1D: Preparation of carboxylic acid modified silica nanoparticles: 650 grams of ASN was placed into a 32 ounce clear glass jar. A Teflon coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was started. 198.7 grams of the carboxylic acid silane / DMF solution prepared as described in step 1B above was slowly added to the jar and stirring was continued for an additional 20 minutes. The stir bar was removed and the jar was sealed and placed in a preheated oven at 80° C. for 24 hours to complete the carboxylic acid surface modification of the silica nanoparticles and form a nanodispersion of surface modified silica nanoparticles.
[0205] PE-2: Preparation of (meth)acrylic aqueous dispersions Step 2A: Preparation of NaOH stock solution: 3,000 grams of DI H2O was placed into a 1 gallon clear glass jar. A Teflon coated stir bar was added to the jar. The jar was placed on a stir plate and stirring was started. 1,167 grams of Sodium Hydroxide (NaOH) was slowly added to the jar. The NaOH pellets dissolved in the water forming a clear solution. The Teflon coated stir bar was removed from the jar.
[0206] Step 2B: Preparation of 5 wt% (meth)acrylic polymer MP-1 aqueous dispersion: 1,403 grams of DI H2O was placed in a 2 liter glass reaction flask. 22 grams of 28 wt% NaOH solution was added to the flask as described in step 2A above. Stirring was started and 75 grams of MP-1 was added to the flask. The reaction flask equipped with a reflux column was heated to 100°C. Within 2.5 hours, the MP-1 pellets dissolved in the basic aqueous solution formed a clear dispersion. The MP-1 dispersion was filtered through a 200 micrometer filter.
[0207] Step 2C: Preparation of 15 wt% (meth)acrylic polymer MP-1 aqueous dispersion: 1,208 grams of DI H2O was placed in a 2 liter glass reaction flask. 67 grams of 28 wt % NaOH solution was added to the flask as described in step 2A above. Stirring was started and 225 grams of MP-1 was added to the flask. The reaction flask equipped with a reflux column was heated to 100°C. Within 2.5 hours, the MP-1 pellets dissolved in the basic aqueous solution formed a clear dispersion. The MP-1 dispersion was filtered through a 200 micrometer filter.
[0208] Step 2D: Preparation of 25 wt% (meth)acrylic polymer MP-1 aqueous dispersion: 1,013 grams of DI H2O was placed in a 2 liter glass reaction flask. 112 grams of 28 wt% NaOH solution was added to the flask as described in step 2A above. Stirring was started and 375 grams of MP-1 was added to the flask. The reaction flask equipped with a reflux column was heated to 100°C. Within 2.5 hours, the MP-1 pellets dissolved in the basic aqueous solution formed a clear dispersion. The MP-1 dispersion was filtered through a 200 micrometer filter.
[0209] Step 2E: 15 wt% (meth)acrylic polymer MP-1 aqueous dispersion: 27.6 kilograms of DI H2O was placed in a 3.785 liter stainless steel reactor. 5.1 kilograms of MP-1 pellets were added to the reactor. Agitation was started. 1.5 kilograms of 28 wt% NaOH solution was added to the reactor as described in step 2A. Agitation was increased to 30-60 revolutions per minute. The kettle was sealed and the reactor contents were heated to 100°C. Within 2.5 hours, the MP-1 pellets dissolved in the aqueous basic solution formed a clear dispersion. The MP-1 aqueous dispersion was filtered through a 200 micron filter.
[0210] Step 2F: 15% (meth)acrylic polymer blend of MP-1 and MP-10 aqueous dispersions: 27.6 kilograms of DI H2O was placed in a 3.785 liter stainless steel reactor. 5.1 kilograms of MP-1 pellets were added to the reactor. 2.9 kilograms of MP-10 pellets were added to the reactor. Agitation was started. 1.5 kilograms of 28 wt% NaOH solution was added to the reactor as described in step 2A. Agitation was increased to 30-60 revolutions per minute. The kettle was sealed and the reactor contents were heated to 150°C. Within 2.5 hours, the MP-1 and MP-10 pellets dissolved in the basic aqueous solution formed a milky white dispersion. The MP-1 / MP-10 aqueous dispersion was filtered through a 200 micron filter.
[0211] Preparation of nanodispersions: Step 3A: 10 / 90 surface modified nanoparticles / MP-1 nanodispersion: 600 grams of MP-1 dispersion at 15 wt% copolymer, as described in step 2C above, was placed into a 32 ounce clear glass jar. 53 grams of silica nanodispersion at 18.8 wt% nanoparticles, as described in step 1C above, was added to the jar. The MP dispersion and silica nanodispersion were immediately mixed together to form the nanodispersion.
[0212] Step 3B: 20 / 80 Surface Modified Nanoparticles / MP-1 Nano Dispersion: 533 grams of MP-1 dispersion at 15 wt% copolymer, as described in step 2C above, was placed into a 32 ounce clear glass jar. 106 grams of silica nanodispersion at 18.8 wt% nanoparticles, as described in step 1C above, was added to the jar. The MP aqueous dispersion and silica nanodispersion were immediately mixed to form the nanodispersion.
[0213] Step 3C: 30 / 70 surface modified nanoparticles / MP-1 nano dispersion: 467 grams of MP-1 dispersion at 15 wt% copolymer, as described in step 2C above, was placed into a 32 ounce clear glass jar. 160 grams of silica nanodispersion at 18.8 wt% nanoparticles, as described in step 1C, was added to the jar. The MP dispersion and silica nanodispersion mixed easily to form the nanodispersion.
[0214] Step 3D: 40 / 60 surface modified nanoparticles / MP-1 nano dispersion: 400 grams of MP-1 dispersion at 15 wt% copolymer, as described in step 2C above, was placed into a 32 ounce clear glass jar. 213 grams of silica nanodispersion at 18.8 wt% nanoparticles, as described in step 1C above, was added to the jar. The MP dispersion and silica nanodispersion were immediately mixed together to form the nanodispersion.
[0215] Step 3E: 50 / 50 surface modified nanoparticles / MP-1 nano dispersion: 333 grams of MP-1 dispersion at 15 wt% copolymer, as described in step 2C above, was placed into a 32 ounce clear glass jar. 266 grams of silica nanodispersion at 18.8 wt% nanoparticles, as described in step 1C above, was added to the jar. The MP dispersion and silica nanodispersion were immediately mixed together to form the nanodispersion.
[0216] Step 3F: 60 / 40 surface modified nanoparticles / MP-1 nano dispersion: 257 grams of MP-1 dispersion at 15 wt% copolymer, as described in step 2C above, was placed into a 32 ounce clear glass jar. 319 grams of silica nanodispersion at 18.8 wt% nanoparticles, as described in step 1C above, was added to the jar. The MP dispersion and silica nanodispersion were immediately mixed together to form the nanodispersion.
[0217] Preparation of nanocomposites: Comparative Example CE-1: MP-1 Polymer: 30 grams of MP was inserted into a model D-51 Plasticorder (C.W. Brabender The melt was processed in batch mode using a 350-nm Centrifugal Separator (Mitsubishi Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125° C. for 15 minutes.
[0218] Comparative Example CE-1A: 10 / 90 Surface Modified Nanoparticles / MP-1 Nanocomposite: The nanodispersion prepared in step 3A was filtered through a 200 micrometer filter while being transferred to a shallow aluminum tray and dried at ambient temperature and pressure for a minimum of 3 days. Sixty grams of the dried material was melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125°C for 15 minutes.
[0219] Comparative Example CE-1B: 20 / 80 Surface Modified Nanoparticles / MP-1 Nanocomposite: The nanodispersion prepared in step 3B was filtered through a 200 micrometer filter while being transferred to a shallow aluminum tray and dried for a minimum of 3 days at ambient temperature and pressure. Sixty grams of the dried material was melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125°C for 15 minutes.
[0220] Comparative Example CE-1C: 30 / 70 Surface Modified Nanoparticles / MP-1 Nanocomposite: The nanodispersion prepared in step 3C was filtered through a 200 micrometer filter while being transferred to a shallow aluminum tray and dried at ambient temperature and pressure for a minimum of 3 days. Sixty grams of the dried material was melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125°C for 15 minutes.
[0221] Comparative Example CE-1D: 40 / 60 Surface Modified Nanoparticles / MP-1 Nanocomposite: The nanodispersion prepared in step 3D was filtered through a 200 micrometer filter while being transferred to a shallow aluminum tray and dried at ambient temperature and pressure for a minimum of 3 days. Sixty grams of the dried material was melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125°C for 15 minutes.
[0222] Comparative Example CE-1E: 50 / 50 Surface Modified Nanoparticles / MP-1 Nanocomposite: The nanodispersion prepared in step 3E was filtered through a 200 micrometer filter while being transferred to a shallow aluminum tray and dried at ambient temperature and pressure for a minimum of 3 days. Sixty grams of the dried material was melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125°C for 15 minutes.
[0223] Comparative Example CE-1F: 60 / 40 Surface Modified Nanoparticles / MP-1 Nanocomposite: The nanodispersion prepared in step 3F was filtered through a 200 micrometer filter while being transferred to a shallow aluminum tray and dried at ambient temperature and pressure for a minimum of 3 days. Sixty grams of the dried material was melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 75 rpm and 125°C for 15 minutes.
[0224] Preparation of nanocomposite films: Comparative Example CE-2: MP-1 Polymer Film: The copolymer of Comparative Example CE-1 was pressed into a film using a Model 3856 hot press (Carver Inc., Wabash, Ind.) operated at 125° C. and 82.7 MPa.
[0225] Comparative Examples CE-3 to CE-8: Surface-modified nanoparticles / MP-1 nanocomposites: The nanocomposites of Comparative Examples CE-1A through CE-1F were pressed into films using a Model 3856 hot press (Carver Inc., Wabash, Ind.) operated at 125° C. and 82.7 MPa.
[0226] The pressed nanocomposite films CE-3 through CE-8 and the unfilled MP-1 film of comparative example CE-2 were characterized for thickness, optical properties, and selected mechanical properties of tensile modulus, elongation at break, and pen drop as a measure of impact resistance according to the test methods described below. The characterization results are shown in Table 2.
[0227] [Table 2]
[0228] The film characterization results in Table 2 show that the unfilled MP-1 film of Comparative Example CE-2 exhibits good optical performance with high transmittance and transparency, and low haze, and poor mechanical properties as indicated by poor pen drop performance and low tensile modulus. The SiO2 / MP-1 nanocomposite films of Comparative Examples CE-3 to CE-8 also exhibit good optical performance with high transmittance and transparency, and low haze even at very high nanoparticle loadings. The optical performance demonstrates the effectiveness of the carboxylic acid surface modification of the silica nanoparticles to prevent weak or strong aggregation of the nanoparticles within the matrix. The mechanical properties of the nanocomposite films are superior to the unfilled polymer with better impact resistance, as characterized by pen drop and dramatically higher tensile modulus, even at low nanoparticle loadings. The elongation at break of the nanocomposite films decreases dramatically with increasing nanoparticle loading. The nanocomposite films of Comparative Examples CE-6 to CE-8 exhibited good optical performance and generally good drop, but were too brittle to be properly cut for tensile testing.
[0229] Comparative Examples CE-9 to CE-19: (Meth)acrylic copolymer films of MP-1 to MP-12 The unfilled copolymers and ionomers of Comparative Examples CE-9 to CE-19 were melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 10 minutes. The melt processed materials were cooled to room temperature and then pressed into films using a Model 3856 hot press (Carver Inc., Wabash, IN) operated at 125° C. and 82.7 MPa. The unfilled copolymers and ionomers of Comparative Examples CE-9 to CE-19 were characterized for thickness, optical properties, and selected mechanical properties of tensile modulus, elongation at break, and pen drop. Characterization results are shown in Table 3.
[0230] [Table 3]
[0231] The copolymers and ionomers of Comparative Examples CE-2 and CE-9 to CE-19 all exhibit high transmission and clarity, and low haze. Pen drop results show that all unneutralized copolymers of Comparative Examples CE-2 and CE-9 to CE-11 exhibit poor impact resistance. The ionomer of Comparative Example CE-16, which is a terpolymer, also exhibits poor impact resistance. All ionomers of Comparative Examples CE-12 to CE-15 and CE-17 to CE-19 exhibit better impact resistance compared to the unneutralized copolymers. All ionomers of Comparative Examples CE-12 to CE-19 also exhibit higher tensile modulus compared to the unneutralized copolymers, except for two ionomers of the terpolymers, Comparative Examples CE-16 and CE-19. Neutralization does not have a significant effect on the high elongation at break in the case of all unfilled polymers of Comparative Examples CE-9 to CE-19.
[0232] Comparative Examples CE-20 to CE-30: (Meth)acrylic copolymer blend films The unfilled copolymer and ionomer blends of Comparative Examples CE-20 through CE-30 were melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 10 minutes. The composition of the blends was 44 weight percent MP-1, and 56 weight percent of the second copolymer or ionomer. In each case, 22 grams of MP-1 and 28 grams of the second copolymer or ionomer were combined in the Plasticorder. The melt processed blends were cooled at room temperature and then pressed into films using a Model 3856 hot press (Carver Inc., Wabash, IN) operated at 125° C. and 82.7 MPa. The unfilled copolymer and ionomer blends of Comparative Examples CE-20 through CE-30 were characterized for thickness, optical properties, and selected mechanical properties of tensile modulus, elongation at break, and pen drop. The characteristic evaluation results are shown in Table 4.
[0233] [Table 4]
[0234] All of the unfilled (meth)acrylic copolymer blends of Comparative Examples CE-20-CE-30 exhibit good optical quality with high transmission and clarity, and low haze except for CE-21-CE-23. The haze of Comparative Examples CE-21-CE-23 indicates that the MP-3 and MP-2 copolymers, as well as the MP-5 ionomer, are immiscible with the MP-1 copolymer. The low haze of Comparative Example CE-20 indicates that MP-4 is miscible with MP-1, with the miscibility being determined by the difference in the acid content of the copolymers. The difference in acid chemistry between the copolymers, i.e., acrylic acid and methacrylic acid, does not affect the miscibility. The acid content of the ionomers is believed to be proprietary to the manufacturer. Fortunately, as shown in Table 3, the melting points (T m ) correlates with the acid content, and T m is available for all copolymers and ionomers. Comparative Example CE-23 shows that the MP-5 ionomer is immiscible with the MP-1 copolymer, as indicated by the high haze. The high T m also suggests that the ionomers of Comparative Examples CE-24 to CE-30 have low T m , suggesting high acid content and miscibility with the high acid content MP-1 copolymer. The low haze of comparative examples CE-24-CE-30 confirms this premise.
[0235] The pen drop results for the blends of Comparative Examples CE-20 to CE-30 show that the poor impact resistance of MP-1 is imparted to the blends. Similarly, the tensile modulus of the blends with MP-1 is generally lower than the pure copolymers or ionomers. The elongation at break for all blends remains high.
[0236] Comparative Examples CE-31 to CE-36: MP-1 / MP-10 Blend Films: The MP-1 / MP-10 copolymer / ionomer blends of Comparative Examples CE-31-CE-36 were melt processed in continuous mode using a ZSE 27 MAXX twin screw extruder (Leistritz, Allendale, NJ) at 175° C. and 150 rpm. Residence time in the extruder is estimated to be less than 1 minute. The extrudate was collected at the exit of the extruder as a "pliers sample" and allowed to cool to room temperature. The extrudate was pressed into films using a Model 3856 hot press (Carver Inc., Wabash, IN) operated at 125° C. and 82.7 MPa. The unfilled blends of Comparative Examples CE-31-CE-36 were characterized for thickness, optical properties, and selected mechanical properties of tensile modulus, elongation at break, and pen drop. Characterization results are shown in Table 5.
[0237] [Table 5]
[0238] Optical characterization of comparative examples CE-31 through CE-36 demonstrates the optical grade quality and miscibility of the MP-1 / MP-10 ionomer blends across the blend composition range. Note that the haze is lower when melt processing is performed in continuous mode versus batch mode. This is expected because the batch mode of the Plasticorder requires manual cleaning while the continuous mode of the extruder is self-cleaning. The pen drop results show that the low impact resistance of MP-1 dominates the impact resistance of the blends across the majority of the blend compositions. The tensile modulus of the blends correlates with that of the pure copolymer and ionomer. The elongation at break of the blends is consistent with that of the pure copolymer and ionomer.
[0239] Example 1: Surface-modified nanoparticle / MP-1 / MP-4 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-4 copolymer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150°C and 75 rpm for 15 minutes.
[0240] Example 2: Surface-modified nanoparticle / MP-1 / MP-3 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-3 copolymer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0241] Example 3: Surface-modified nanoparticle / MP-1 / MP-2 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-2 copolymer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150°C and 75 rpm for 15 minutes.
[0242] Example 4: Surface-modified nanoparticle / MP-1 / MP-5 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-5 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0243] Example 5: Surface Modified Nanoparticle / MP-1 / MP-6 Nanocomposite Blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-6 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0244] Example 6: Surface-modified nanoparticle / MP-1 / MP-7 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-7 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0245] Example 7: Surface-modified nanoparticle / MP-1 / MP-8 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F were combined with 20 grams of MP-8 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0246] Example 8: Surface Modified Nanoparticle / MP-1 / MP-9 Nanocomposite Blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-9 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0247] Example 9: Surface-modified nanoparticle / MP-1 / MP-10 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-10 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0248] Example 10: Surface-modified nanoparticle / MP-1 / MP-11 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-11 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0249] Example 11: Surface-modified nanoparticle / MP-1 / MP-12 nanocomposite blends: Forty grams of the 60 / 40 surface-modified nanoparticle / MP-1 nanocomposite of Comparative Example CE-1F was combined with 20 grams of MP-12 ionomer and melt processed in batch mode using a Model D-51 Plasticorder (CW Brabender Instruments, Inc., South Hackensack, NJ) at 150° C. and 75 rpm for 15 minutes.
[0250] Examples 12-22: Nanocomposite Blend Films: The nanocomposite blends of Examples 1-11 were pressed into films using a Model 3856 hot press (Carver Inc., Wabash, Ind.) operated at 125° C. and 82.7 MPa. The nanocomposite blend films of Examples 12-22 were characterized for thickness, optical properties, and selected mechanical properties of tensile modulus, elongation at break, and pen drop. Characterization results are shown in Table 6.
[0251] [Table 6]
[0252] All nanocomposite blends except for Examples 13-15 exhibit high transmittance and clarity, and low haze. The high haze of Examples 13-15 is due to the immiscibility of the two polymers in the nanocomposite blends, as explained with reference to Comparative Examples CE-14-CE-16. The pen drop results show that most of the nanocomposite blends exhibit improved impact resistance versus their blends with pure copolymer, ionomer, or MP-1. The improved impact resistance is due to the nanoparticles. Comparative Examples CE-6-CE-8 showed that the nanoparticles improved the impact resistance, but the nanoparticles also increased the brittleness of the nanocomposite at high loadings. The results of the nanocomposite blends of Examples 12-22 demonstrate how combining blends with nanoparticles results in nanocomposite blends with improved impact resistance without brittleness. The nanocomposite blends of Examples 12-22 have the same nanoparticle loading as Comparative Example CE-6, but are not brittle. The results demonstrate the complementary benefits of polymer blends and polymer nanocomposites in the development of new flexible optical materials.
[0253] Test Method nuclear magnetic resonance (NMR) The synthesized carboxylic acid silane chemistry was confirmed using a Bruker Avance 600 MHz NMR spectrometer equipped with a cryogenically cooled probehead (Bruker Corporation, Billerica, MA). The carboxylic acid silane / DMF solution was mixed with deuterated DMF. One-dimensional (1D) 1 H and 13 C NMR data were collected at 25° C. One of the residual protosolv resonances was used as the secondary chemical shift reference in the proton dimension (δ=8.03 ppm).
[0254] Thermogravimetric analysis (TGA) The nanoparticle concentration in the nanocomposite and nanocomposite blend films was measured by TGA. A model TGA Q500 (TA Instruments, New Castle, DE) was used. Approximately 5 milligrams of nanocomposite film or nanocomposite blend film sample was placed on a platinum pan that had been pre-weighted from the instrument. The nanoparticle concentration was determined as the final weight of the sample after heating from room temperature to 700°C at 20°C / min.
[0255] Film Thickness Film thickness was measured using a digital indicator model H0530E (Mitutoyo America Corporation, Aurora, Ill.).
[0256] Transmission, Haze, and Clarity (THC) Luminous transmittance, haze, and clarity were measured according to ASTM D1003-00 using a Model 4725 Gardner Haze-Guard Plus (BYK-Gardner, Columbia, MD).
[0257] Pen falling Pen drop was measured using a plastic graduated cylinder and a 4.5 gram ballpoint pen. The pen was loaded into the cylinder at the test height, and then the pen was dropped onto the film being tested. The maximum height that left no impact defect from the pen hitting the film was recorded as the pen drop height. The minimum height of the scale on the cylinder was 1 centimeter, and film failure at 1 cm was labeled "<1 cm."
[0258] Tensile Modulus Tensile modulus was measured using a Model 5965 mechanical property testing unit (Instron, Norwood, MA). A film 3 inches (7.6 cm) long by 1 inch (2.54 cm) wide by the measured thickness was loaded between the clamps of the unit. The film was not tapered. The film was stretched at a strain rate of 0.5 inches per minute (1.3 cm / min). Tensile modulus was recorded as the slope of stress versus strain using the 2% offset method.
[0259] Breaking Elongation The elongation at break was measured using a Model 5965 mechanical property testing unit (Instron, Norwood, MA). A film of measured thickness, 3 inches (7.6 cm) long by 1 inch (2.54 cm) wide, was loaded between the clamps of the unit. The film was not tapered. The film was stretched at a strain rate of 0.5 inches per minute (1.3 cm / min). The percentage increase in the strained film length when the film broke was recorded as the elongation at break.
[0260] For purposes of illustration, specific embodiments have been illustrated and described herein, but those skilled in the art will recognize that a wide variety of alternative and / or equivalent implementations may be substituted for the specific embodiments shown and described without departing from the scope of the invention. This application is intended to cover any adaptations or variations of the preferred embodiments described herein. Therefore, it is manifestly intended that the disclosure be limited only by the claims and the equivalents thereof.
Claims
1. a first (meth)acrylic polymer or copolymer comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid; a second (meth)acrylic polymer or copolymer comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid; Formula 1 【Chemistry 1】 (In the formula, R1 is C 1 ~C 10 is an alkoxy group, R2 and R3 are independently C 1 ~C 10 Alkyl group and C 1 ~C 10 alkoxy groups; A is C 1 ~C 10 Alkylene group or arylene group, C 1 ~C 10 Aralkylene group, C 2 ~C 16 Heteroalkylene or heteroarylene groups, and C 2 ~C 16 amido-containing groups. a surface-modified metal oxide nanoparticle having a surface-modified with a surface modifier comprising a carboxylic acid silane of the formula: A nanocomposite blend comprising:
2. 10. The nanocomposite blend of claim 1, wherein the first and second (meth)acrylic polymers or copolymers each comprise a copolymer comprising at least one additional monomer selected from the group consisting of ethylene, propylene, alkyl (meth)acrylates, aryl (meth)acrylates, alkaryl (meth)acrylates, acrylonitrile, and carbon monoxide.
3. 3. The nanocomposite blend of claim 2, wherein the first and second (meth)acrylic polymers are at least partially neutralized with sodium cations, calcium cations, potassium cations, zinc cations, lithium cations, magnesium cations, aluminum cations, or combinations thereof.
4. 3. The nanocomposite blend of claim 2, wherein the (meth)acrylic monomer in the first and second copolymers is present in an amount of at least 14% by weight.
5. 5. The nanocomposite blend of claim 4, wherein the difference in (meth)acrylic acid monomer in said first and said second copolymers is less than 6% by weight.
6. 10. The nanocomposite blend of claim 1, wherein the concentration of said surface-modified metal oxide nanoparticles is from 1 to 70% by weight.
7. 10. The nanocomposite blend of claim 1, wherein said surface-modified metal oxide nanoparticles have an average diameter of from 4 nanometers to 100 nanometers.
8. 2. The nanocomposite blend of claim 1, wherein the surface-modified metal oxide nanoparticles comprise surface-modified nanoparticles of a metal oxide of silicon, titanium, aluminum, hafnium, zinc, tin, cerium, yttrium, indium, antimony, or mixtures thereof.
9. 9. The nanocomposite blend of claim 8, wherein said surface-modified metal oxide nanoparticles comprise surface-modified silica particles.
10. 3. The nanocomposite blend of claim 2, wherein in at least one of said first and second copolymers, said additional monomer comprises ethylene or propylene.
11. 11. The nanocomposite blend of claim 10, wherein at least one of the first and second copolymers further comprises at least one third monomer selected from the group consisting of n-butyl acrylate, isobutyl acrylate, isopropyl acrylate, n-propyl acrylate, ethyl acrylate, methyl acrylate, 2-ethylhexyl acrylate, iso-octyl acrylate, and methyl methacrylate.
12. 10. The nanocomposite blend of claim 1, wherein the carboxylic acid silane is produced by the reaction of an organic acid anhydride with an aminoalkyltrialkoxysilane.
13. 13. The nanocomposite blend of claim 12, wherein the organic acid silane is succinic anhydride.
14. 13. The nanocomposite blend of claim 12, wherein said aminoalkyltrialkoxysilane is 3-aminopropyltrimethoxysilane.
15. 10. The nanocomposite blend of claim 1, wherein the nanocomposite comprises an article in the form of a film, sheet, filament, particle, pellet, flake, or molded article.
16. 1. An optical film article comprising at least one layer of a polymer nanocomposite blend, the polymer nanocomposite blend comprising: a first (meth)acrylic polymer or copolymer comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid; a second (meth)acrylic polymer or copolymer comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid; Formula 1 【Chemistry 2】 (In the formula, R1 is C 1 ~C 10 is an alkoxy group, R2 and R3 are independently C 1 ~C 10 Alkyl group and C 1 ~C 10 alkoxy groups; A is C 1 ~C 10 Alkylene group or arylene group, C 1 ~C 10 Aralkylene group, C 2 ~C 16 Heteroalkylene or heteroarylene groups, and C 2 ~C 16 amido-containing groups. a surface-modified metal oxide nanoparticle having a surface-modified with a surface modifier comprising a carboxylic acid silane of the formula:
1. An optical film article comprising:
17. 17. The optical film article of claim 16, wherein the optical film article is flexible, bendable, rollable, foldable, or moldable.
18. 20. The optical film article of claim 16, wherein the optical film article is a multilayer optical film article.
19. 20. The optical film article of claim 18, wherein the multilayer optical film article further comprises at least one additional layer including a clear functional coating layer, a clear adhesive layer, and one or more removable layers.
20. 20. The optical film article of claim 19, wherein the transparent functional coating comprises a hardcoat layer, a conductive layer, a barrier layer, a microstructured layer, a slip agent layer, an anti-glare layer, an anti-reflective layer, an anti-fingerprint layer, or an anti-sparkle layer.
21. 17. The optical film article of claim 16, wherein the optical film article is optically clear.
22. A display device; 11. An optical article comprising an optical film article in contact with a surface of the display device, the optical film article comprising a flexible, bendable, rollable, foldable, or formable optical film comprising at least one layer of a polymer nanocomposite blend, the polymer nanocomposite blend comprising: a first (meth)acrylic polymer or copolymer comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid; a second (meth)acrylic polymer or copolymer comprised of monomers selected from the group consisting of methacrylic acid and acrylic acid; Formula 1 【Chemistry 3】 (In the formula, R1 is C 1 ~C 10 is an alkoxy group, R2 and R3 are independently C 1 ~C 10 Alkyl group and C 1 ~C 10 alkoxy groups; A is C 1 ~C 10 Alkylene group or arylene group, C 1 ~C 10 Aralkylene group, C 2 ~C 16 Heteroalkylene or heteroarylene groups, and C 2 ~C 16 amido-containing groups. a surface-modified metal oxide nanoparticle having a surface-modified with a surface modifier comprising a carboxylic acid silane of the formula: An optical article comprising:
23. 23. The optical article of claim 22, wherein the optical article comprises a display device having a molded optical film article, the molded optical film article being a molded optical film article.
24. 1. A method of making an optical article comprising preparing a nanocomposite blend, the method comprising: (a) preparing an aqueous nano-dispersion of surface-modified metal oxide nanoparticles, the surfaces of the metal oxide nanoparticles being modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of a first (meth)acrylic polymer or copolymer, the (meth)acrylic polymer or copolymer being at least partially neutralized; (c) combining the dispersions of (a) and (b) to form an aqueous nano-dispersion of the surface-modified metal oxide nanoparticles and the first (meth)acrylic polymer or copolymer; (d) drying and / or concentrating the nanodispersion of (c); (e) melt processing the dried and / or concentrated nano-dispersion (d) and a second (meth)acrylic polymer or copolymer to form a nanocomposite blend of surface-modified metal oxide nanoparticles and (meth)acrylic polymer or copolymer, wherein the surface of the metal oxide nanoparticles has been modified with a carboxylic acid silane surface modifier and the (meth)acrylic polymer or copolymer has been at least partially neutralized; A method comprising:
25. 1. A method of making an optical article comprising preparing a nanocomposite blend, the method comprising: (a) preparing an aqueous nano-dispersion of surface-modified metal oxide nanoparticles, the surfaces of the metal oxide nanoparticles being modified with a carboxylic acid silane surface modifier; (b) preparing an aqueous dispersion of first and second (meth)acrylic polymers or copolymers, wherein the first and second (meth)acrylic polymers or copolymers are at least partially neutralized; and (c) combining the dispersions of (a) and (b) to form an aqueous nano-dispersion of the surface-modified metal oxide nanoparticles and the first and second (meth)acrylic polymers or copolymers; (d) drying and / or concentrating the nanodispersion of (c); (e) melt processing the dried and / or concentrated nano-dispersion (d) to form a nanocomposite blend of surface modified metal oxide nanoparticles and first and second (meth)acrylic polymers or copolymers, wherein the surfaces of the metal oxide nanoparticles are modified with a carboxylic acid silane surface modifier and the first and second (meth)acrylic polymers or copolymers are at least partially neutralized; A method comprising:
26. 25. The method of claim 24, wherein the formed nanocomposite blend comprises an optical film.
27. 27. The method of claim 26, wherein the formed nanocomposite blend optical film is optically clear and nominally colorless.
28. 27. The method of claim 26, wherein the formed nanocomposite blend optical film has a luminous transmittance of greater than 85% and a haze value of less than 10%.